Gryllotalpa weisei Simeu-Noutchom & Kekeunou sp. nov. and the first record of Gryllotalpa microptera (Chopard 1939) (Orthoptera, Gryllotalpidae) from Cameroon with redescription of the species - Simeu-Noutchom, Alain; Kekeunou, Sevilor; Wandji, Alain Christel; Nzike, Marcelle Mbadjoun; Ngoute, Charly Oumarou; Messi, Nadege Brigitte Mbezele; Tamesse, Joseph Lebel (Zootaxa, 2020)
Gryllotalpa weisei Simeu-Noutchom & Kekeunou sp. nov. was collected only in Tombel in the South-West region of Cameroon, during a survey conducted from March 2016 to March 2018 in the West, South-West and Centre regions of Cameroon. This species is close to Gryllotalpa microptera, collected for the first time in Cameroon during these investigations, only in the West region. G. weisei is different from G. microptera due to the hind wings that are vestigial; average fore wings length of 5.85±0.56 mm in male and 5.34±0.45 mm in female, not reaching the fifth abdominal segment; anal end of fore wings slightly concave; a stridulatory file with 54±8.02 teeth (47–71) in average, fairly spaced, with an average of 30±5.06 teeth per millimeter; hind tibia bearing 11 spines; internal process of ectophallus quite short. G. weisei abounds in mixed crop fields, followed by cocoa agro-forests; it is scarce in grassy fallows and in forest undergrowth. G. microptera was present in all types of vegetations in Bafoussam, Babeté and Bangoulap in the West region where it has been abundant in mixed crop fields, grass-fallow and coffee agro-forest but rare in forest undergrowth.